Predictors of Teachers’ Self-Efficacy in Teaching EFL: An Examination of “Nativeness” and Teachers’ Training - Gao, Yan; Gumah, Bernard; Kulbo, Nora B.; Addo, Prince Clement; Kulbo, Dora B.; Aziabah, Maxwell A. (Frontiers in Education, 2021)
The study aimed to establish the link between teacher training and “nativeness” on teachers’ self-efficacy in teaching English as a second language. By applying a teacher’s sense of efficacy scale, we measured the self-efficacy of a total of 281 foreign teachers in Chengdu, China. We adopted MANOVA and tested the influence of “nativeness” and teachers’ training on teachers’ self-efficacy. Our analysis shows that while being a native speaker does not necessarily influence a teacher’s self-efficacy, trained teachers have higher self-efficacy than untrained teachers. Thus, the current study lends credence to the view that language proficiency should not be allied with being a language teacher. Instead, educational administrators and policymakers should focus on language teachers’ professional development rather than emphasizing the native/non-native teachers’ distinction.